127k views
4 votes
Can anyone do this with steps ..

Can anyone do this with steps ..-example-1

1 Answer

4 votes


\\ \sf\longmapsto \displaystyle{\lim_(x\to 0)}(sinx-sin3x)/(sins3x-sinx)


\boxed{\sf \displaystyle\lim_(x\to 0)(f(x))/(g(x))=(\lim_(x\to 0)f(x))/(\lim_(x\to 0)g(x))}

Now


\\ \sf\longmapsto \displaystyle{(\lim_(x\to 0)sinx-\lim_(x\to 0)sin3x)/(\lim_(x\to 0)sin3x-\lim_(x\to 0)sinx)}


\boxed{\sf \displaystyle{\lim_(x\to 0)}f(x)=f(a)}


\\ \sf\longmapsto (sin0-sin3(0))/(sin3(0)-sin0)


\\ \sf\longmapsto (0-0)/(0-0)


\\ \sf\longmapsto (0)/(0)


\\ \sf\longmapsto 0

User Dqw
by
5.2k points